The influence of dribbling on repeated sprints in young soccer players - Meckel, Y.; Geva, A.; Eliakim, A. (International Journal of Sports Science and Coaching, 2012)
The purpose of the study was to examine the effect of soccer dribbling on performance indices and physiological responses during repeated sprints (6 x 30-m) test, in straight and slalom run, of young (13.1±0.4 y) soccer players. In the straight run repeated sprints test: Ideal (fastest) sprint time and total sprint time were significantly faster without dribbling (37.24±2.56 versus 40.68±2.84 and 38.50±2.47 versus 41.78±2.81 s, p<0.001, respectively). There was no significant difference in performance decrement between repeated sprints test with and without dribbling. Maximal heart rate and blood lactate concentrations were significantly higher in repeated sprints test without dribbling (185±17 versus 178±12 beat/min and 8.7±0.3 versus 6.9±0.6 mmol/l, p<0.05, respectively). In the slalom run repeated sprints test: ideal sprint time and total sprint time were significantly reduced (50.58±3.04 versus 73.30±5.59 and 51.63±2.83 versus 74.05±5.75 s, p<0.001, respectively) and performance decrement significantly greater without dribbling (2.12±1.55 vs 1.02±1.40 %, p<0.001, respectively). Blood lactate concentration was significantly higher in repeated sprints test without dribbling (8.6±0.6 versus 6.9±0.8 mmol/l, p<0.05, respectively). There was no significant difference in maximal heart rate between repeated sprints test with and without dribbling. There were no significant differences in repeated sprints test performance indices in straight and slalom runs with and without dribbling between defensive and offensive players and between starting squad and substitute players. It was concluded that the additional motor tasks due to dribbling and slalom reduce speed and physiological responses in repeated maximal short sprints. Anaerobic fitness capabilities, dribbling skills and anthropometric measures are unable to distinguish between starting squad or substitute players, and between offensive and defensive players at this age.